Pengaruh Kondisi Sosial Ekonomi Rumah Tangga Terhadap Status Putus Sekolah Anak Di Indonesia - Agusti, Rahma Dwi; Marta, Joan; Idris, Idris (Universitas Negeri Padang, 2025)
This study aims to analyze: (1) How does the occupation of the head of the household affect the dropout status of children, (2) How does the number of household members affect the dropout status of children, (3) How does the employment status of the head of the household affect the dropout status of children, (4) How does the poverty status of the head of the household affect the dropout status, (5) How does the area of residence affect the dropout status, (6) What is the effect of parental completeness on dropout status, (7) What is the effect of Indonesia Smart Card ownership on child dropout status, (8) What is the effect of working child status on child dropout status, (9) What is the effect of birth order on dropout status, (10) What is the effect of child disability on child dropout status. The data used in this study are cross section data collected from the 2020 SUSENAS KOR data. This research method uses logistic regression analysis technique. Based on the results of this study, it shows that the education of the head of the household, the occupation of the head of the household, the receipt of KIP and disability have a negative and significant effect on the dropout status of children and the variables of the number of children in the household, poverty, region, parental completeness, children's occupation, birth order have a positive and significant effect on the dropout status of children in Indonesia.